Bioremediation of electroplating industrial wastewater using bioenzymes generated from citrus - Simranpreet Kaur Natt; Priya Katyal; Urmila Gupta Phutela; Sumita Chandel (Environment Conservation Journal)
Industries involved in electroplating have a significant potential for contamination of water sources and soil. The indiscriminate release of effluents from electroplating enterprises into natural aquatic systems poses a major hazard to the flora and fauna. Using bioenzymes in wastewater treatment is an effective and eco-friendly approach. In this work, we employed bioenzymes derived from citrus fruit peels to treat the electroplating industry effluent. The effluent was subjected to bioenzymes digestion at concentrations of 1%, 5%, 6%, and 10% at room temperature (25°C), with periodic sampling for analysis of various parameters over a 20-day treatment period. The analysis included changes in pH, electrical conductivity (EC), biological oxygen demand (BOD), chemical oxygen demand (COD), and total dissolved solids (TDS). Additionally, the elemental profile of the bioenzymes-treated and control effluent samples was determined. The results demonstrated that bioenzymes can reduce the pH, EC, BOD, COD, and TDS of the effluent, while 10% of bioenzymes reduced ferrous (Fe) by 99.19%, phosphorous (P) by 63.02%, arsenic (As) by 98.72%, and sulfur (S) by 60.79%.  The reductions were statistically significant at 6% and 10% concentrations. Following the treatment with bioenzymes, the concentration of As, Fe, and Pb in the treated effluent fell below the permissible limit for effluent discharge. This study demonstrates that bioenzymes can serve as a cost-effective and environmentally friendly solution to improve the quality of wastewater, making it suitable for safe disposal. To improve the effectiveness of bioenzymes for treating wastewater, more research should be done to find the best additives, activators, and enzyme cocktails. This should include pre-treatment strategies and an examination of how they affect different wastewater properties and metal pollutant removal.